MULTIMETRIC INDICES BASED ON VEGETATION DATA FOR ASSESSING ECOLOGICAL AND HYDROMORPHOLOGICAL QUALITY OF A MAN-REGULATED LAKE - Bolpagni, R. (Annali di Botanica, 2013)
A functional characterization of the littoral and shore vegetation was performed in the Lake Idro to assess its ecological quality and hydromorphological alteration. A detailed survey of hydro-hygrophilous vegetation was carried out in 2010-2012. Three multimetric indices were calculated: the MacroIMMI (the Italian macrophytic index for mid-size subalpine lakes with a maximum depth < 125 m), the SFI (Shorezone Functional Index), and the LHS (Lake Habitat Survey). The MacroIMMI (0.76) classified the lake in a good ecological status, although the dominant aquatic species were exotic (Elodea nuttallii and Lagarosiphon major). The SFI pointed out that the 50% of total shorelines displayed a very good or excellent conservation status; conversely, the LHS revealed high levels of morphological alteration coupled with rather good levels of habitat diversity, likely due to the high colonization rates of macrophytes along the lake shore. The lacustrine multimetric indices seem suitable for assessing the conservation status of mid-size lakes. However, for the present case-study, the metrics used require further implementation to suit the peculiarities of Italian subalpine lakes.